Skeletal-related events significantly impact health-related quality of life in metastatic castration-resistant prostate cancer: data from PREVAIL and AFFIRM trials - Saad, F (Prostate Cancer Prostatic Dis, 2017)
BACKGROUND: We investigated the impact of skeletal-related events (SREs) on health-related quality of life (HRQoL) in patients with metastatic castration-resistant prostate cancer (mCRPC) in phase III trials of enzalutamide versus placebo. METHODS: Patients with mCRPC experiencing at least one SRE during AFFIRM and PREVAIL were assessed for trajectory-adjusted mean change in HRQoL by first SRE using Functional Assessment of Cancer Therapy-Prostate (FACT-P; AFFIRM, three domains, and PREVAIL, nine domains) and EQ-5D (PREVAIL) instruments. RESULTS: First SREs caused HRQoL deterioration in both trials. Spinal cord compression had the largest impact, with clinically meaningful reductions in seven of nine FACT-P domains in PREVAIL and all three in AFFIRM (mean (95% confidence interval (CI)) change in FACT-P total score –16.95 (–26.47, –7.44) and –9.69 (–16.10, –3.27), respectively). In PREVAIL, first SREs caused clinically meaningful declines in EQ-5D utility index, irrespective of category; spinal cord compression had the largest impact (mean (95% CI) change –0.24 (–0.39, –0.08)). In AFFIRM, FACT-P and FACT-General total scores showed clinically meaningful declines after radiation/surgery to bone. CONCLUSIONS: SREs were associated with clinically meaningful functional declines in the daily lives of patients with mCRPC. Spinal cord compression had the largest impact on HRQoL.